Desafiando as versões da História: reavaliações da Guerra do Vietnã nas obras In the Lake of the Woods (2006) e Going After Cacciato (2014), de Tim O’Brien - Freitas, Yohan Fagundes de [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Esta pesquisa objetiva analisar como o autor estadunidense Tim O’Brien, um veterano da Guerra do Vietnã, abordou as vivências desse doloroso capítulo histórico em suas obras In the Lake of the Woods (2006) e Going After Cacciato (2014). Explorando a proposta de reavaliação dos fatos proporcionada pela ficção pós-moderna, o estudo objetiva lançar luz sobre um dos períodos mais controversos da História dos Estados Unidos. Sob a perspectiva do pós-modernismo, a análise das estratégias narrativas empregadas por O’Brien fundamenta-se em teorias de Hutcheon (1986, 2001, 2004), Jameson (1997, 1998, 2002), White (1973, 1985, 1987), Said (1994), entre outros. A pesquisa busca não somente examinar as narrativas ficcionais de O’Brien, mas também refletir sobre como a Literatura pode ser uma ferramenta essencial na apresentação de múltiplas perspectivas para fatos históricos. A investigação procura estabelecer conexões entre a metaficção historiográfica, termo cunhado por Hutcheon, as representações da Guerra do Vietnã e as contribuições específicas das obras In the Lake of the Woods e Going After Cacciato no processo de reavaliação da História oficial.

This study aims at analyzing the ways in which the American author Tim O´Brien, a veteran of the Vietnam War, addresses the experiences of this painful historical moment in his novels In the Lake of the Woods (2006) and Going After Cacciato (2014). By exploring the notion of fiction as a means of reevaluating facts offered by postmodernism, the study seeks to shed light on one of the most controversial periods in the United States history. From a postmodern perspective, the analysis of the narrative techniques employed by O´Brien is based on theories by Hutcheon (1986, 2001, 2004), Jameson (1997, 1998, 2002), White (1973, 1985, 1987), Said (1994), among others. This investigation endeavors endeavors not only to examine these works of fiction written by O´Brien, but also to reflect upon how Literature can be an essential tool for historical reassessment through multiple perspectives. The investigation aims to establish connections between historiographical metafiction, concept coined by Hutcheon, representations of the Vietnam War, and the specific contributions of In the Lake of the Woods and Going After Cacciato in the process of reevaluating official History.
Challenging Historical Narratives: Reassessments of the Vietnam War in Tim O’Brien's Works In the Lake of the Woods (2006) and Going After Cacciato (2014)
Keywords: In the Lake of the Woods; Going After Cacciato; Tim O’Brien; Guerra do Vietnã; Metaficção Historiográfica; Pós-Modernismo; Vietnam War; Historiographical Metafiction; Postmodernism